Family Social Capital as a Determinant of Student Motivation and Academic Achievement - Huda, Mahrus; Hariani, Mila; Masnawati, Eli (Journal of Social Science Studies, 2024)
Family social capital is an important foundation for student academic achievement because it shapes how students understand the value of education, how they interact with the school environment, and how they manage academic pressure. This article aims to analyses the relationship between family social capital and student academic achievement by highlighting family social networks, family communication patterns, and the forms of social support received by children. This study was conducted through qualitative literature review using thematic synthesis by examining academic publications in the last two decades. The analysis was carried out by identifying communication patterns, family support structures, and social networks that have a direct relationship with academic achievement. The results show that strong family social networks support students' emotional stability and expand access to learning resources. Warm family communication patterns help students develop confidence in facing academic tasks and foster intrinsic motivation to learn. Emotional support from the family has been shown to increase students' perseverance in overcoming learning obstacles and encourage consistent academic orientation. In addition, relationships between family members based on open dialogue create a psychological foundation that provides a sense of security for students in carrying out their roles as learners. This study confirms that learning success cannot be separated from the quality of interactions within the family. When families provide emotional support, clear messages, and stable social relationships, students show improvements in focus, motivation, and academic achievement. These findings highlight the importance of strengthening communication between parents and children for a more effective learning process. This article provides a theoretical contribution to the development of studies on family social capital and provides a practical basis for educators and parents in building a family environment that can support children's academic development.